Perbedaan Persepsi Mahasiswa Terhadap Kompetensi Preceptor Klinik Dan Preceptor Akademik pada Stase Keperawatan Dasar Profesi (KDP) Program Studi Ners Stikes Guna Bangsa Yogyakarta - Widuri Widuri (LPPM STIKES Guna Bangsa, 2019)
Background: Clinical practice in nursing is an opportunity for all students to translate theoretical knowledge into actual action. In the clinic environment, students jwill be motivated by the suitability of competencies carried out through active participation in clinical learning, while thinking, action, and professional attitudes are played by clinical counselors (preceptors). Objective: To know the difference between student perceptions of clinical preceptor competency and academic preceptor on Basic Nursing Professional Stase. Research Method: This type of research uses descriptive comparative with cross sectional method. The population of this study was all Ners profession students. The research sample amounted to 48 respondents taken using the total sampling technique. Data collection uses questionnaires and the results of statistical tests used are T-test analysis. Results: Based on the research, students 'perceptions of clinical preceptor competency in the medium category were 32 (66.7%) and the students' perceptions of academic preceptor competencies in the high category were 26 (54.2%). The results of the analysis of the T test (t-test), obtained the value of tcount = 0.006. Thus the value of tcount <0.05, it is stated that the hypothesis Ha is accepted. Conclusion: There is a difference between student perceptions of clinical preceptor competency and academic preceptor on Basic Nursing Professional Stase (KDP).